THE VITAL ROLE OF ACCOUNTING AND AUDITING IN THE DIGITAL ECONOMY (Journal of Universal Science Research, 2024)
In the digital economy, characterized by rapid technological advancements and globalization, accounting and auditing play indispensable roles in ensuring transparency, accountability, and trust in financial transactions. This article explores the significance of accounting and auditing in the digital era, examining their role in enhancing financial reporting, ensuring compliance and risk management, and fostering innovation and adaptability. Through advanced technologies and methodologies, businesses can leverage accounting and auditing practices to navigate the complexities of the digital landscape and drive sustainable growth.